2012
DOI: 10.1016/j.surg.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Is BRAF mutation associated with lymph node metastasis in patients with papillary thyroid cancer?

Abstract: Background Some have proposed using V600E BRAF mutation status to dictate the surgical management of patients with papillary thyroid cancer (PTC). However, well-designed studies examining BRAF association with aggressive clinicopathologic features of PTC, including the presence of lymph node metastases (LNM), in patients who have undergone routine central lymph node dissection (CLND), are lacking. Methods Under institutional review board approval, 63 patients diagnosed with PTC on fine-needle aspiration who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…These results support the hypothesis that the coexistence of CLT counteracts tumor progression and recurrence in PTC (Loh et al 1999, Kim et al 2009a, Lang et al 2014. Furthermore, there were previous studies that did not demonstrate the association between BRAF mutation and aggressive clinicopathological characteristics of PTC (Lee et al 2012a,b, Gouveia et al 2013, Kim et al 2015. These studies could explain why the impact of CLT was not different according to BRAF mutation status.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results support the hypothesis that the coexistence of CLT counteracts tumor progression and recurrence in PTC (Loh et al 1999, Kim et al 2009a, Lang et al 2014. Furthermore, there were previous studies that did not demonstrate the association between BRAF mutation and aggressive clinicopathological characteristics of PTC (Lee et al 2012a,b, Gouveia et al 2013, Kim et al 2015. These studies could explain why the impact of CLT was not different according to BRAF mutation status.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies have demonstrated a strong association between the BRAF mutation and aggressive clinicopathological characteristics of PTC such as advanced stage, extrathyroidal extension (ETE), lymph node (LN) metastasis and tumor recurrence (Kebebew et al 2007, Lupi et al 2007, Xing 2007. However, there were other studies that did not demonstrate the association between the BRAF mutation and aggressive clinicopathological characteristics of PTC (Lee et al 2012a,b, Gouveia et al 2013, Kim et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent subgroup of classical and follicular variants of PTC showed no association of BRAF mutation with poor prognostic factors or poor outcome. Our findings corroborated recent studies (20,21,22,23) and also discarded the association of p.V600E with higher frequency of cervical LN and distant metastases (13,24,25,26). In order to justify the lack of association, it has also been proposed that it is not the intratumoral presence of BRAF mutation that determines prognosis but the higher frequency of mutant BRAF alleles, identified in an innovatory analysis of pyrosequencing technique, that favors more frequent recurrence (27).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecsupporting
confidence: 90%
“…The debate centers on whether the BRAF V600E mutation portends a higher risk of metastatic disease in the central compartment, and whether it should be used as a criterion for pCLND. Data are conflicting, because some studies have found BRAF V600E to be an independent predictor of central lymph node metastases [31], whereas others have not [32]. More data are likely needed here [33].…”
Section: Management Of Regional Lymph Nodesmentioning
confidence: 99%